Knowledge and Perspectives of Postgraduate Nurses regarding Competency of Advanced Nursing Practice in Kurdistan Region of Iraq - Bootan Hasan Ahmed; Ribwar Arsalan Mohammed; Sanaa Hassan Abdulsahib; Vian Afan Naqshbandi (Erbil Journal of Nursing and Midwifery, 2018)
Background and objectives: Advanced nursing practice (ANP) involves integration role domains, which are related to clinical practice, education, research, professional development and organizational leadership. The objectives of this study were to assess the knowledge and perspective of graduated nurse regarding competency of advanced nursing practice and explain the domains of advanced nursing practice competency.